The Contents of Nineteen Chemical Elements in Thyroid Malignant Nodules and Thyroid Tissue adjacent to Nodules investigated using X-Ray Fluorescence and Neutron Activation Analysis : Chemical elements in thyroid tissue adjacent to malignant nodule - Zaichick, Vladimir (Jour Med Resh and Health Sci, 2022)
Background: Thyroid malignant nodules (TMNs) are the most common endocrine cancer and the fifth most frequently occurring type of malignancies. The etiology and pathogenesis of TMNs must be considered as multifactorial. Objectives: The present study was performed to clarify the role of some chemical elements (ChEs) in the etiology of these thyroid disorders. Methods: Thyroid tissue levels of nineteen ChEs including silver (Ag), calcium (Ca), chlorine (Cl), cobalt (Co), chromium (Cr), cooper (Cu), iron (Fe), mercury (Hg), iodine (I), potassium (K), magnesium (Mg), manganese (Mn), sodium (Na), rubidium (Rb), ammonium (Sb), scandium (Sc), selenium (Se), strontium (Sr), and zinc (Zn) were prospectively evaluated in malignant tumor and tissue adjacent to tumor of 41 patients with TMNs. Measurements were performed using a combination of non-destructive methods X-ray fluorescence and instrumental neutron activation analysis with high resolution spectrometry of short- and long-lived radionuclides. Results of the study were additionally compared with previously obtained data for the same ChEs in “normal” thyroid tissue. Results: The common characteristics of TMNs in comparison with “normal” thyroid and visually “intact” thyroid tissue adjacent to malignant tumors were elevated levels of Cl and K, as well as drastically reduced level of I. Furthermore, the ChEs composition of thyroid tissue adjacent to tumor did not equal ChEs contents of “normal” thyroid. Moreover, contents of such elements as Ag, Hg, I, and Se in adjacent tissue were higher than in tumor. Conclusions: The excessive accumulation of Ag, Hg, I, and Se by thyroid tissue is likely to precede the TMNs origination and development. Elevated levels of Cl and K, as well as drastically reduced level of I in cancerous tissue could possibly be explored for differential diagnosis of benign and malignant thyroid nodules